Analisis Kinerja Perusahaan Transportasi Dan Otomotif Di Bursa Efek Indonesia Tahun 2012-2013 - Pertiwi, Githa, Muzakar Isa, S.E., M.Si (2015)
This research purposes to know what method is advantage between economic value added and return on asset to performance of transportation and automotive firms go public in Indonesia Stock Exchange year 2012 - 2013. Analysis of this research uses quantitative collecting with documentation. Method economic value added (EVA) is more advantage that shows PT Astra International Tbk reaches highest. While PT Indospring Tbk reaches highest value with return onf asset (ROA). But return on asset (ROA) valued is less advantage to measure firm' performance because this ratio is size befit if manager want to evaluation how much fund so decisions increase investment and decrease profit firm.